2008
DOI: 10.1097/qai.0b013e318189a794
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Activation Markers Are Linked to HIV Status and Are Independent of Antiretroviral Therapy and Lipoatrophy

Abstract: Objectives To assess the association of inflammatory and endothelial activation biomarkers with the presence of lipoatrophy in HIV-infected subjects and to examine the role of HIV, antiretroviral therapy (ART), and metabolic parameters in endothelial activation and inflammation. Design Prospective, cross-sectional study including 4 groups: HIV+ on ART with HIV-1 RNA <1000 copies/mL with and without clinical lipoatrophy, HIV+ ART naive, and healthy controls. Methods We measured plasma levels of inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 59 publications
4
49
2
Order By: Relevance
“…A recent study found a potential association between heightened circulating inflammatory markers and markers of endothelial activation, 27 but our study using brachial FMD showed no such associations with inflammatory markers. Indeed, we did not show a correlation of circulating markers of endothelial activation with our physiologic measure of endothelial function.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…A recent study found a potential association between heightened circulating inflammatory markers and markers of endothelial activation, 27 but our study using brachial FMD showed no such associations with inflammatory markers. Indeed, we did not show a correlation of circulating markers of endothelial activation with our physiologic measure of endothelial function.…”
Section: Discussioncontrasting
confidence: 53%
“…8 More contemporary studies in which few subjects received indinavir have failed to confirm a role for PI-containing antiretroviral regimens in endothelial dysfunction 14 or endothelial activation. 27 In fact, there was a nonsignificant trend for better endothelial function measured by brachial FMD among subjects receiving PIs (predominantly nelfinavir and lopinavir-ritonavir) in the study of Solages and colleagues.…”
mentioning
confidence: 99%
“…This is consistent with recent findings of a close relationship between inflammation due to uncontrolled viremia/advanced HIV disease and a higher risk of CV disease and endothelial dysfunction. [11][12][13] As ART prolongs the lives of HIV-infected adults, understanding the pathogenesis of CV disease in this population is essential. Further studies are needed to explore the role of MPO in HIV-infected adults and establish useful biochemical markers in this high-risk group.…”
mentioning
confidence: 99%
“…It was reported that myeloperoxidase activity was significantly higher in HIV infected subjects on HAART than HAART naïve subjects [22]. But Ross et al [23] observed elevated myeloperoxidase activity in HIV infected adults both on HAART and HAART naïve. In HIV infection, the expected and appropriate inflammatory response to an infectious process may be amplified and the risk of secondary infection increases.…”
Section: Discussionmentioning
confidence: 98%